Lab-scale Evaluation of Two Biotechnologies to Treat VOC Air Emissions: Comparison with a Pilot Unit Installed in the Plastic Coating Sector - Álvarez-Hornos, F. Javier; Sempere, Feliu; Izquierdo, Marta; Gabaldón, Carmen (IntechOpen, 2011)
None